Effects of post heat treatment on the microstructure evolution of Inconel 718 manufactured by selective laser melting - Tao Song; Zhixiang Xue; Guanbing Ma; Yang Chen; Shuxian Yuan; Chenglin Li; Yangsen Hu; Jun Zhang (Materials Research Express, 2021)
In this work, the microstructure, precipitations, crystal orientation and texture of an Inconel 718 superalloy manufactured by selective laser melting (SLM) are investigated by performing post heat treatment. Horizontal and vertical reference faces are examined in the as-built condition, solution conditions for 0.5 and 1 h, and aging condition, respectively. In the as-built condition, Inconel 718 superalloy exhibited cellular and columnar dendrites, a large amount of the fine Laves phase, and several γ ′ phases. During post treatment, the grain size on the horizontal face is changed, which is ranged from 502.23 to 523.55 μ m ^2 per grain. Meanwhile, grains coarsened distinctly on the vertical face. The average area of the grain is 739.48 μ m ^2 in the as-built condition and increases to 898.19 μ m ^2 in the aging condition. Additionally, the amount of MC carbides, γ ′, and γ ″ strengthening phases increased as well during the post heat treatment process, while that of the Laves phase decreased after solution treatment. The preferred orientation on the horizontal face was 〈111〉//X, 〈001〉//Y in the as-built condition, and 〈101〉//Z in the solution and aging conditions. The preferred orientation on the vertical face was 〈001〉//X, 〈101〉//Y in the as-built condition, 〈101〉//Y in the solution condition, and 〈001〉//X in the aging condition. The orientation distribution function (ODF) analysis showed that the main textures in the as-built and solution conditions were {110}〈110〉 and {110}〈112〉, respectively, which transformed to {001}〈100〉 and {001}〈110〉 during aging. The values of multiples of uniform density (mud) in both horizontal and vertical reference faces the aforementioned preferred orientation and texture increased during post heat treatment. Application of post heat treatment can lead to an ideal microstructure Inconel 718 superalloy manufactured by SLM.